Study of DNA double strand break repair in Dictyostelium discoideum - Lempidaki, S (2012)
The homologous recombination (HR) pathway contributes to genome integrity by mediating double strand break (DSB) repair using a homologous DNA sequence as a template. In mammals Rad51 and Brca2 are molecules central to this process. Little is known about HR repair in Dictyostelium. However, research previously conducted on DSB repair using this organism has shown that DSB repair pathways are highly conserved when compared to humans. This encouraged study of HR in this organism. In this study, through a bioinformatics search I have identified putative orthologues of most human HR proteins and most interestingly of BRCA2, which cannot be found in other lower eukaryotes used as models for DSB repair, such as the budding yeast S.cerevisiae. Brcp, the Dictyostelium BRCA2 ortholog, shows similar domain structure when compared to BRCA2-related proteins identified in other organisms. To verify the implication of HR proteins in DSB repair, I developed a method to monitor recruitment of DNA repair proteins on chromatin upon DSB induction. Findings of this study suggest that both Brcp and Rad51 get recruited to chromatin upon DSB induction and are therefore implicated in DSB repair in Dictyostelium. To further study Brcp function and based on findings suggesting that disruption of brcp might be lethal, I developed a novel system for specific and conditional depletion of endogenous Dictyostelium proteins. Utilizing this system, I conducted phenotypic studies in a strain depleted of Brcp to examine its role in DNA repair. Overall this study shows that the HR pathway in Dictyostelium shows great similarity to vertebrates, making Dictyostelium an appealing model for the study of DSB repair and specifically HR.